EFFECTS OF CORE BODY MUSCULAR STRENGTH TRAINING ON BOULDERING ROCK CLIMBING PERFORMANCE - Chumpornpan, Kiatkumtorn; Tengku Sulaiman, Raja Syed; Choeychom, Kongkiat (Academic Journal of Thailand National Sports University, 2023)
The purpose of this research was to study and compare the effects of core strength training on bouldering rock climbing performance. The samples used in this research were 30 elite bouldering rock climbing athletes. The instrument used in this research was the 4 routes test of moon climbing. The statistics for the data analysis consisted of the mean, standard deviation, one - way repeated measures ANOVA, and Bonferroni multiple comparison test (Bonferroni’s test). The significance level was set at 0.05. The results showed that there were significant differences in bouldering rock climbing performance of the elite athlete’s as the experimental group among before, after 4 and 8 weeks of training sections at .05 level. Moreover, the bouldering rock climbing performance after 8 weeks of training section was higher than that after 4 week and before training section respectively, while the performance as mentioned of the control group was not different. Apart from that, this study was also found that there were significant differences in bouldering rock climbing performance between the experimental and control groups both after 4 and 8 weeks of training sections at .05 level, while the performance mentioned between both at before training sections was not different.